Politics and Firm Boundaries: How Organizational Structure, Group Interests, and Resources Affect Outsourcing - Bidwell, Matthew J. (Organization Science, 2012)
How does managers' pursuit of their own intraorganizational interests affect decisions about what work to outsource and how to contract with vendors? I study this question using a qualitative study of outsourcing in the information technology department of a large financial services firm. Traditional transaction cost-based theories argue that decisions about which transactions to outsource should reflect the characteristics of those transactions, yet I find only a weak link between transaction characteristics and outsourcing decisions. Qualitative evidence suggests that managers' pursuit of their own intraorganizational interests helps to explain why outsourcing decisions were often divorced from transaction characteristics. I found that the consequences of outsourcing projects were consistent with the assumptions of transaction cost and capabilities-based theories: managers had less authority over outsourced projects than internal ones, those projects were subject to weaker administrative controls, and outsourced vendors provided different capabilities than internal suppliers. However, the way that those consequences were evaluated often reflected managers' own interests rather than those of the organization. I highlight three aspects of organizational structure that affected how managers evaluated outsourcing: the nature of differentiated goals and responsibilities, the administrative controls that managers faced, and the pressures caused by interdependent workflows within the organization. I also show how the distribution of authority and other resources shaped which projects were outsourced. The analysis highlights the value of understanding make-or-buy decisions as an endogenous consequence of the structure in which those decisions take place, rather than as isolated decisions that are maximized regardless of their context.